Design and Manufacturing of Single Sloped Solar Still: Study the Effect of Inclination Angle and Water Depth on Still Performance - Aljubouri, Ali A (Al-Nahrain Journal of Science, 2017)
he most prominent factors that have a significant influence on the performance of solar distillation are the inclination angle of the solar still cover and the water depth within the still basin. This paper was investigated an experimental performance of a single solar still. Five single sloped solar stills were designed and fabricated to operate under Baghdad city weather condition during August 2016. The inner dimensions of each basin were 0.5x0.5 m. The glass covers were tilted at 20o, 31o, 45o and 50o with respect to the horizontal. The temperatures of the outer glass covers surfaces were measured. Also, this study presents an experimental investigation on the potable water collection amount with the water depths of 1, 2, 3, 5, and 7 cm into each still basin and the different glass lid inclination angles. The hourly amount of extracted drinkable water was monitored. The daily produced amounts of fresh water increased by reducing the tilt angle from 50o to 20o, and diminish of water depth in the basin from 7 cm to 1 cm. The highest total daily amount was 495 ml/day ( 2 l/m2/day) for solar still with tilt angle of 20o and water depth of 1 cm.